Pengaruh Jub Arti Sempit (M1), BI Rate, Inflasi, dan Kurs Terhadap IHSG di Bursa Efek Indonesia - Delia Intan Gojali; Endang Hatma Juniwati; Leni Nur Pratiwi (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The research aims to know the effect of Narrow Money, Interest Rate of Bank Indonesia, inflation, and exchange rate towards Composite Stock Price Index (CSPI) in 2016-2020. Sampling of the reseach was CSPI in 2016-2020, the type of data used is time series with monthly data collection taken from 2016-2020, with n research data as much as 60. Research methodology using descriptive method with quantitative approachment. Data analysis technique used are multilinear regression with data processing assisted using data processing application The research showed that Narrow Money had a positive effects and significant toward Composite Stock Price Index (CSPI) , Interest Rate of Bank Indonesia had a not significant effect toward Composite Stock Price Index (CSPI), Inflation had a positif effects and significant toward Composite Stock Price Index (CSPI), and exchange rate had a negative effects and significant toward Composite Stock Price Index (CSPI). Simultaneously that Narrow Money, Interest Rate of Bank Indonesia, inflation, and exchange rate had a significant effect towards Composite Stock Price Index (CSPI)